Assessing Attitude Toward COVID-19 Vaccination in South Korea - Acharya, Shiva Raj; Moon, Deog Hwan; Shin, Yong Chul (Frontiers in Psychology, 2021)
Vaccines are the most effective strategy to safeguard against COVID‐19 and it is crucial to assess community acceptance of COVID-19 vaccination. This exploratory study aimed to assess the attitude of immigrants towards the acceptance of COVID-19 vaccines in South Korea. A web-based anonymous study was completed by 463 immigrants. The data were statistically analyzed using a logistic regression model and ANOVA test. On a scale of 0-6, the average attitude toward the COVID-19 vaccination was 4.17±1.73, indicating generally positive attitudes. The proportion of the immigrants who were certain to get COVID-19 vaccination was 55.3%. Only 36.7 % reported that the COVID-19 vaccines are safe. Of the immigrants, 72.6% showed high acceptance and 27.4% low acceptance towards the COVID-19 vaccines. Vaccine safety concern was the major predictor for COVID-19 vaccine acceptance. Up-to-date, valid information on COVID-19 vaccine safety, and vaccine risk communication strategies are required to increase vaccine acceptability.